DOP45 Utilization and sustainability of biologics in CD - A nationwide study from the epi-IIRN. (27th May 2021) - Atia, O; Yogev, D; Chagit, F; Gili, F; Orlanski-Meyer, E; Magen Rimon, R; Natan, L; Shira, G; Kariv, R; Yisca, L W; Gabay, H; Nevo, D; et al.
Abstract: Background: Real-world studies demonstrate that ~33% of CD patients fail to respond to induction therapy with biologics. In this nationwide study we aimed to evaluate trends in biologics utilization and sustainability in CD during the last 15 years. Methods: This study was performed on data from the four Israeli Health Maintenance Organizations, covering 98% of the population. Sustainability was defined as continuous treatment without IBD-related surgeries and at most one short steroid course. Sustainability was compared across different biologics utilizing a propensity score (PS) weighted analysis, estimated by generalized boosted modeling (GBM). Results: 16, 936 patients were diagnosed with CD in Israel since 2005 (2, 932 [17%] pediatric-onset, 14, 004 [83%] adult-onset), of whom 5, 804 (34%) were ever treated with biologics (1, 659 [57%] pediatric-onset, 4, 145 adults [30%], OR 3.1 [95%CI 2.9–3.4]) with a median of 6.4 years follow up (IQR 3.4–9.9). Infliximab was the most common first-line treatment in children (58%, p<0.001), while adalimumab was the most common in adults (63%, p<0.001). However, in recent years there was an increase in adalimumab and vedolizumab utilization in parallel with a decrease in infliximab (Figure). The rate of initiating biologics in the first year of diagnosis increased from 20% among all biologics users during 2005–2010 through 36% during 2011–2014 and 74% since 2015 (p<0.001). The use of combination therapy with immunomodulators is becoming less common in last years and decreased in infliximab from 38% until 2010 to 21% in 2018 (P<0.001) and in adalimumab from 22% to 7%, respectively (p<0.001). The sustainability rate in those treated with infliximab was 65% at one year from initiation of biologics, and 46% and 42% at three and five years, thereafter; compared to 72%, 61% and 57% with adalimumab and 84% and 80% after one and two years in vedolizumab. The rate of primary non-response was 21% with infliximab, 17% with adalimumab and 12% with vedolizumab. Sustainability was associated with male sex (HR 0.9 [95%CI 0.8–0.95]) and earlier initiation of biologics (HR 0.92 [95%CI 0.9–0.95]). In the PS-adjusted model the sustainability of both infliximab (HR 0.7 [95%CI 0.6–0.8]) and vedolizumab (HR 0.8 [95%CI 0.7–0.95]) were lower than adalimumab. Compared with monotherapy, combination therapy did not change significantly the sustainability rate of all three biologics (adalimumab: HR 1.3 [95%CI 0.8–2.1], infliximab: HR 1.2 [95%CI 0.7–1.9], and vedolizumab: HR 0.8 [95%CI 0.5–1.3]). Conclusion: Biologics are being increasingly used in CD and earlier during the disease course, but most patients do not sustain treatment at five years. Sustainability rate was higher with adalimumab compared with either infliximab or vedolizumab